Toward Engineering Biosystems With Emergent Collective Functions - Gorochowski, Thomas E.; Hauert, Sabine; Kreft, Jan-Ulrich; Marucci, Lucia; Stillman, Namid R.; Tang, T.-Y. Dora; Bandiera, Lucia; Bartoli, Vittorio; Dixon, Daniel O. R.; Fedorec, Alex J. H.; Fellermann, Harold; Fletcher, Alexander G.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Many complex behaviours in biological systems emerge from large populations of interacting molecules or cells, generating functions that go beyond the capabilities of the individual parts. Such collective phenomena are of great interest to bioengineers due to their robustness and scalability. However, engineering emergent collective functions is difficult because they arise as a consequence of complex multi-level feedback, which often spans multiple length-scales. Here, we present a perspective on how some of these challenges could be overcome by using multi-agent modelling as a design framework within synthetic biology. Using case studies covering the construction of synthetic ecologies to biological computation and synthetic cellularity, we show how multi-agent modelling can capture the core features of complex multi-scale systems and provide novel insights into the underlying mechanisms which guide emergent functionalities across scales. The ability to unravel design rules underpinning these behaviours offers a means to take synthetic biology beyond single molecules or cells and towards the creation of systems with functions that can only emerge from collectives at multiple scales.